Microincision aponeurotic ptosis surgery of upper lid - Kuzmanović Elabjer, Biljana; Bušić, Mladen, liječnik; Elabjer, Esmat; Sekelj, Sandra; Kondža-Krstonijević, Edita (2009)
Abstract: The paper is a prospective study of 23 lids of 20 patients with upper lid aponeurotic ptosis operated using microincision technique in period 2005-2008. There were 7 males and 13 females. Age of the patients was 28–83 years (y), average 61±17 y, for female 63±13.4 y and for male 61±19 y. Inclusion criteria were: aponeurotic upper lid ptosis more than 2 mm, no other lid abnormalities, minimal dermatochalasis, no previous or concomitant lid surgery. The procedure was performed in local anesthesia through 10 mm cut. Aponeurosis was fixated to the tarsal plate with two sutures. Success was considered if operated lid height differed up to 0.5 mm of the other eye and margin-to-reflex distance was 2–4 mm in primary position. Postoperative results regarding contour, skin crease and lash position were good in all patients. Regarding height, 19/23 (83%) met criteria of 0.5 mm of the other eye and MRD 2–4 mm. In one bilateral procedure there was an asymmetry of 1 mm. Three patients with unilateral procedure had at least 1mm asymmetry comparing to the other eye. Reoperation was neccessary in two bilateral cases. Lid fold was symmetrical only in 7 patients (35%). The rest had slight to grose lid fold asymmetry. Complications were scarce, in early postoperative period there was hematoma in two patients lasting up to three weeks. Late failure was noticed in two cases 6 and 8 months postoperatively. Advantages are: less anesthetic results in less decreased levator function and more accurate assessment of eyelid position intraoperatively, less distortion of the lid due to less bleeding and edema, shorter operation time, less scarring and shortened recovery time. However it can be used only in selective cases
Bibliografija: 13 jed
Sažetak
Keywords: Aponeuroza -- Vjeđa -- Mikroincizijska operacija